Differential protease content of mast cells and the processing of IL-33 in Alternaria alternata induced allergic airway inflammation in mice - Krysko, Olga; Korsakova, Darya; Teufelberger, Andrea; De Meyer, Amse; Steels, Jill; De Ruyck, Natalie; van Ovost, Judith; Van Nevel, Sharon; Holtappels, Gabriele; Coppieters, Frauke; Ivanchenko, Mikhail; Braun, Harald; et al. (Frontiers in Immunology, 2023)
Background Recent in vitro studies strongly implicated mast cell-derived proteases as regulators of IL-33 activity by enzymatic cleavage in its central domain. A better understanding of the role of mast cell proteases on IL-33 activity in vivo is needed. We aimed to compare the expression of mast cell proteases in C57BL/6 and BALB/c mice, their role in the cleavage of IL-33 cytokine, and their contribution to allergic airway inflammation. Results In vitro, full-length IL-33 protein was efficiently degraded by mast cell supernatants of BALB/c mice in contrast to the mast cell supernatants from C57BL/6 mice. RNAseq analysis indicated major differences in the gene expression profiles of bone marrow-derived mast cells from C57BL/6 and BALB/c mice. In Alternaria alternata (Alt) - treated C57BL/6 mice the full-length form of IL-33 was mainly present, while in BALB/c mice, the processed shorter form of IL-33 was more prominent. The observed cleavage pattern of IL-33 was associated with a nearly complete lack of mast cells and their proteases in the lungs of C57BL/6 mice. While most inflammatory cells were similarly increased in Alt-treated C57BL/6 and BALB/c mice, C57BL/6 mice had significantly more eosinophils in the bronchoalveolar lavage fluid and IL-5 protein levels in their lungs than BALB/c mice. Conclusion Our study demonstrates that lung mast cells differ in number and protease content between the two tested mouse strains and could affect the processing of IL-33 and inflammatory outcome of Alt -induced airway inflammation. We suggest that mast cells and their proteases play a regulatory role in IL-33-induced lung inflammation by limiting its proinflammatory effect via the IL-33/ST2 signaling pathway.